Photocatalytic treatment techniques using titanium dioxide nanoparticles for antibiotic removal from water - Duarte, António A. L. S. (2017)
The increasing of emerging micropollutants presence in drinking water sources have brought new challenges to existing water treatment systems (WTS), highlighting the need of innovative and low-cost technological solutions. Recent advances in nanotechnology enable highly efficient and multifunctional processes, providing sustainable alternatives to current water treatment practices. This chapter presents the results of several pilot-scale studies developed to assess the effects of TiO2 nanoparticles on antibiotic removal efficiency, using different low-cost photocatalytic reactors. The characterization of its photo-oxidation kinetics also performed considering different test scenarios in order to assess the effects of the major abiotic parameters on oxytetracycline (OTC) removal efficiency, which achieved the maximum values of 96% and 98% using the photocatalysis with TiO? and the photocatalytic filtration, respectively. It must be highlighted the surprising regeneration ability showed by the photocatalytic porous medium, developed at a lab-scale, which can completely recover its oxidative properties after few hours of simple sun exposure.